The Effect of Transformational Leadership and Organizational Culture on Lecturer Performance Through Innovative Work Behavior at Catholic Universities in Surabaya - Bernardus Aris Ferdinan; Tuty Lindawati (AIBPM Publisher, 2021)
This paper aims to investigate the effect of transformational leadership and organizational culture on innovative behavior and work performance. The sample consisted of 204 lecturers from three catholic universities in Surabaya. The data were obtained from Google form and analyzed using Structural Equation Modeling (SEM) with LISREL program. The results of the study indicate that transformational leadership has a negative and significant effect on innovative work behavior, organizational culture has a positive and significant effect on innovative work behavior, innovative work behavior has a positive and significant effect on performance, transformational leadership has a negative and significant effect on performance, organizational culture has a positive effect and significant on performance, transformational leadership has a negative and insignificant effect on performance through innovative work behavior, and organizational culture has a positive and significant effect on performance through innovative work behavior. It suggests the university leaders apply appropriate leadership styles, maintain and enhance their organizational culture.